Economic Aspects in the Management of Diabetic Macular Edema in Italy - Giovanna Elisa Calabrò; Giovanna Elisa Calabrò; Michele Basile; Monica Varano; Filippo Amore; Roberto Ricciardi; Francesco Bandello; Americo Cicchetti (Frontiers Media S.A., 2022)
BackgroundDiabetic Macular Edema (DME) is the most common cause of vision loss in diabetic patients. Currently, the Vascular Endothelial Growth Factor inhibitors (anti-VEGFs) are used as the first line of DME treatment and corticosteroid implants are usually used as a second-line treatment. These implants are a safe and effective therapeutic option that can improve the quality of life of DME patients by reducing the intravitreal injections number. We determined the economic impact related to DME, also from the social perspective, and the consequences of the increased use of the dexamethasone implant.MethodsThe analysis compares two scenarios: the first based on the current rate of recourse to the therapeutic alternatives available in the Italian healthcare setting (as is) and the second based on the assumption of an increased recourse to dexamethasone implants (to be). The results are expressed both in terms of the resource absorption associated with the two scenarios and in terms of the cost differential yielded by their comparison.ResultsThe increased use of the dexamethasone implant allows considerable savings in terms of healthcare professionals' time, follow-up and productivity lost by patients/caregivers. These savings would reduce healthcare costs for the management of DME patients in Italy by €2,058,238 in 5 years.ConclusionsTo optimize the healthcare resources allocation, it is necessary to implement treatments that yield not only cost reductions but also a clinical benefit for patients. The dexamethasone implant use is an example of DME management that generates value for patients, health system and society.